Association Between Wound Healing and Psycho-Emotional State Among Postoperative Patients - Klevinskienė, Ilona; Andrejeva, Julija (Slauga. Mokslas ir praktika, 2022)
Wound healing is a difficult process, it can be complicated by experiences that can occur during pre-operative and post-operative periods. Emotions have a substantial influence on human behaviour and health. Therefore, it is important to study interaction of wound healing and psychoemotional state, in order to obtain efficient wound treatment and care in Lithuania. Aim of the work - to evaluate interface of postoperative patients of wound healing and psycho-emotional state. Methods. A mixed study was conducted, combining quantitative and qualitative research methods. Instruments used: questionnaire (Minnesota Multiphasic Personality Inventory (MMPI-2) test and the Lüscher color test) and medical document analysis (used to identify wound healing type). Statistical analysis of research data performed using statistical software package SPSS 17.0 and Microsoft Excel 2016. Research sample – 383 respondents. Research conducted in accordance with the principle of ethics. Results. The study revealed that women reported higher levels of post-operative state anxiety. Men tend to value their psycho-emotional stress levels more favourably. Also, data analysis revealed that there was an increase in men interaction with environment during post-operative period. Female respondent group showed statistically significant dependence between concomitant illnesses and wound healing, when concomitant illnesses affected wound healing in a negative way. There was a dominance of secondary intention wound healing in respondents (male and female) who had higher levels of post-operative psycho-emotional stress. Conclusions. Taken together, findings indicate that negative psycho-emotional experiences during post-operative period affect wound healing in a negative way, slowing down the healing process.